The Role of Digital Competence in the Educational System of the 21st century - Curca, Mirela (Didactica Danubiensis, 2023)
This paper is the result of a synthesis about the role of digital competence in pre-university and university education in an era where digitization has transformed and reformed society. In the context of the pandemic, the importance of digital competence has become vital for education systems all over the world , which is talked about to this day about technology facilitated teaching.